CONCEPTUAL PROVISIONS FOR FORMING A MECHANISM FOR ENSURING THE ECONOMIC SECURITY OF AGRICULTURAL ENTERPRISES - LYTVYNENKO, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article updates and analyzes the issues of managing the economic security of enterprises whose main economic activity is agriculture. The purpose of the study is to generalize the conceptual provisions of the formation of a mechanism for ensuring the economic security of agricultural enterprises. It is shown that the analysis of the economic security of agricultural enterprises begins with a thorough study of external and internal threats. The relevance of applying a systemic approach when ensuring the economic security of agricultural enterprises is indicated. It is argued that such an approach requires the identification of a system of elements of the mechanism for ensuring the thermal security of agricultural enterprises. It is shown that in the context of the development of the agricultural sector of Ukraine, the decisive factor for success is the flexibility and adaptability of management strategies used by agricultural enterprises. It has been proven that as agricultural enterprises face the constant need to adapt to changing economic and environmental conditions, their survival and development depend on the ability to innovate and effectively manage available resources. This includes not only technological innovations, but also social and organizational transformations that can strengthen interpersonal relationships and increase overall productivity and profitability. It is proven that the practical testing of the policy of ensuring the economic security of an agricultural enterprise involves the formation and implementation of an appropriate management mechanism as a complex system of interconnected elements and specific measures to achieve specific goals. The implementation of the mechanism requires the identification of its elements, subjects and objects, methods, tasks, technologies, organizational processes and regulations, etc. Such a mechanism is an integrated system of management actions for the development and implementation of strategic and tactical measures, ensuring the stability of the enterprise in a changing external environment.
Keywords: economics and business management; agricultural enterprises; economic security; provision mechanism; management; strategic management; sustainability; viability; challenges; risks and threats